CATALYST SELECTION AND TECHNOLOGY FOR THE PRODUCTION OF METHANOL AND DIMETHYL ETHER BASED ON LOCAL RAW MATERIALS - Shukurov, Jasur; Bakhtiyorov, Dilshod; Abdugapparova, Durdona; Qosimova, Dilshoda; Muhamadjonova, Mokhina (Collection of scientific papers «ΛΌГOΣ», 2025)
The work used Al2O3*CuO*ZnO*ZrO2//HSZ and CuO*Al2O3*ZnO//HSZ catalysts with the following composition for methanol synthesis. Two-flow devices were used to conduct catalytic experiments: 2-4 MPa in the pressure range and 0.2-0.6 MPA (low pressure device) in the range. Catalyst activation was conducted in a nitrogen-hydrogen stream (≈2 Vol.% H2 at N2, consumption ≈2 l/h). Contact Time, s∙kgkat/l defined by formula: τ=3600m/Vkir, conversion of methanol to dimethyl ether (DME) calculated by formula: ХСН3ОН = 2СDME∙100(2СDME+ См).The conversion of methanol to DME rises as contact duration increases (volumetric velocity decreases). Pressure reduction reduces the rate of methanol production but has no effect on methanol dehydration. As a result, the higher the methanol synthesis, the lower the pressure at the same contact time.